Ultrasensitive and Broadband All‐Optically Controlled THz Modulator Based on MoTe2/Si van der Waals Heterostructure. Issue 17 (26th May 2020) - Qiao, Jie; Wang, Shanpeng; Wang, Ziming; He, Chuan; Zhao, Shuqi; Xiong, Xixi; Wang, Shilei; Zhang, Xixia; Tao, Xutang
Abstract: Despite the impressive progresses in terahertz (THz) sources and detection, there is still a big challenge for high performance active optoelectronic THz devices such as THz modulators. All‐optically controlled THz modulators with large modulation depth (MD) and wide modulation bandwidth are of great importance for the THz technology. Herein, a MoTe2 /Si van der Waals (vdWs) heterostructure is rationally designed as all‐optical THz modulator by taking advantage of their similar band alignment and easy integration with Si complementary metal‐oxide‐semiconductor (CMOS). The MoTe2 /Si modulator presents an ultrasensitive THz modulation performance with a MD of 99.9% under a low illumination power of 300 mW at 1064 nm. This is a record MD for TMDCs‐based all‐optically controlled THz modulators to date. Moreover, the MoTe2 /Si modulator exhibits broadband modulation performance with a wide frequency range from 0.3 to 2.0 THz. The high modulation performance under low illumination power is beneficial for practical application with low energy consumption and easy heat dissipation, which is advantageous to modulator chip. This work validates a facile protocol for fabricating high performance THz modulators and paves the way for their practical applications in THz technology. Abstract : All‐optically controlled MoTe2 /Si THz modulators based on liquid exfoliated MoTe2 are experimentally investigated. The MoTe2 /Si modulators present excellent performance with ultrasensitive and broadband modulation. The modulation depth is as large as 99.9% even under a very low illumination power of 300 mW and the modulation bandwidth covers the wide frequency range from 0.3 to 2.0 THz.